Effects of vaccination against reproductive diseases on reproductive performance of lactating dairy cows submitted to AI - Pereira, M. H C [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Alfieri, A. A.; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier, 2013)
Four experiments evaluated the effects of vaccination against bovine herpesvirus-1 (BoHV-1), bovine viral diarrhea virus (BVDV), and Leptospira spp. on reproductive performance of lactating dairy cows without (experiments 1, 2, and 3) or with previous vaccination against these diseases (experiment 4). Cows were assigned to a fixed-time AI protocol (FTAI; d -11 to 0) in all experiments, as well as AI 12. h upon estrus detection in experiment 3. Pregnancy status was determined with transrectal ultrasonography on d 30 and 71 (d 60 for experiment 3) after AI. Pregnancy loss was considered in cows pregnant on d 30 but non-pregnant on the subsequent evaluation. In experiment 1, 853 cows received (VAC) or not (CON) vaccination against BoHV-1, BVDV, and Leptospira spp. at the beginning of the FTAI (d -11) and 30. d after AI. Pregnancy loss was reduced (P=0.03) in VAC cows compared with CON. In experiment 2, 287 cows received VAC or CON 30. d prior to (d -41) and at the beginning (d -11) of the FTAI. Pregnancy rates on d 30 and 71 were greater (P≤0.03) in VAC cows compared with CON. In experiment 3, 1680 cows with more than 28. d in milk were randomly assigned to receive VAC or CON with doses administered 14. d apart, and inseminated within 15-135. d after the second dose. Pregnancy rates on d 30 and 60 were greater (P≤0.02) in VAC cows compared with CON. In experiment 4, 820 cows received (REVAC) or not (CON) revaccination against BoHV-1, BVDV, and Leptospira spp. at the beginning of the FTAI protocol (d -11). Pregnancy rates and loss were similar (P≥0.54) between treatments. Hence, vaccinating naïve cows against BoHV-1, BVDV, and Leptospira spp. improved reproductive efficiency in dairy production systems, particularly when both doses were administered prior to AI. © 2013 Elsevier B.V.
Keywords: Dairy cows; Reproductive diseases; Reproductive performance; Vaccine; animal; animal disease; artificial insemination; Bovine diarrhea virus; Bovine herpes virus; bovine viral diarrhea; Brazil; cattle; female; herpes virus infection; immunology; lactation; Leptospira; leptospirosis; methodology; pregnancy; randomization; regression analysis; reproduction; standard; vaccination; virology; Animals; Bovine Virus Diarrhea-Mucosal Disease; Cattle; Diarrhea Viruses, Bovine Viral; Female; Herpesviridae Infections; Herpesvirus 1, Bovine; Insemination, Artificial; Lactation; Least-Squares Analysis; Leptospirosis; Pregnancy; Random Allocation; Reproduction; Vaccination; Bos; Bovinae; Bovine herpesvirus 1; Bovine viral diarrhea virus 1; Human herpesvirus 1